Nutritional Evaluation of Meat Biryani – a Popular and Most Consumed Delicacy - Kuna, Aparna; Sreedhar, M.; Jagan, Ch.; Rani, D. Sharanya; Bhagyamma, M.; Sandhya, V. (Journal of Meat Science, 2019)
Biryani is a delicious energy dense dish that is revealed pan India. The aim of this study was to analyze the nutrient content of biryani  (chicken, mutton and beef) and to understand the nutritional composition along with fatty acid and amino acid composition. The nu tritional analysis of biryani indicates that the energy content was 434.656 ± 13.76 K.Cal / 100g, with 18.30 ± 2.90g/100g fat and 16.54  ± 3.93 g/100g protein content. The saturated, unsaturated and trans fat (%) content was 37.08 ± 9.44, 61.64 ± 9.61 and 1.28 ± 0.35%  respectively. There was presence of essential amino acids along with semi essential amino acids. As per statistics, biryani is the most  consumed food through online orders as well as restaurant dining, and consumers have to be cautious about the high calorie and fat  content of biryani.
Keywords: Biryani; Nutritional content; Energy dense; Fatty acids; Amino acids